2018
DOI: 10.3892/mmr.2018.8422
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of cyclosporin A against spinal cord injury in rats with hyperglycemia

Abstract: The present study aimed to explore the therapeutic effects of cyclosporin A (CsA) on spinal cord injury (SCI) in rats with hyperglycemia and to identify a novel potential method to treat SCI in the presence of hyperglycemia. Female Sprague-Dawley (SD) rats were randomly allocated into four groups: Sham, SCI, SCI+hyperglycemia and SCI+hyperglycemia+CsA groups. Streptozotocin-induced hyperglycemic SD rats and a weight-drop contusion SCI model were established. The Basso, Beattie, Bresnahan scale and inclined pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The drugs were effective in the order FK506 > minocycline > CsA throughout. Earlier studies have also used BBB scoring along with other behavioral parameters and have shown significant behavioral functional outcome in the SCI animals treated with FK506 [7,22,60,67,69,70,74,76], minocycline [22,28,[43][44][45], and CsA [18,52,53,58,61]. In addition to the therapeutic effects of the three drugs, it has been also suggested that the daily routine behavioral assessment procedures may also assist the animals as equivalent to their exercises that help them to recover from SCI [107].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The drugs were effective in the order FK506 > minocycline > CsA throughout. Earlier studies have also used BBB scoring along with other behavioral parameters and have shown significant behavioral functional outcome in the SCI animals treated with FK506 [7,22,60,67,69,70,74,76], minocycline [22,28,[43][44][45], and CsA [18,52,53,58,61]. In addition to the therapeutic effects of the three drugs, it has been also suggested that the daily routine behavioral assessment procedures may also assist the animals as equivalent to their exercises that help them to recover from SCI [107].…”
Section: Discussionmentioning
confidence: 99%
“…CsA has also been reviewed and reported as a potent neuroprotectant for functional recovery from SCI [5,55]. The significant protective role of CsA has been reported for recovery from SCI through inhibiting the apoptosis of spinal cord cells [53], improving locomotor function [58], increasing mean arterial pressure [110], inhibiting NOS [56], diminishing demyelination and neuronal cell death [60], attenuating reactive astrocytosis due to injury improved neurologic outcome [50], and reducing pain [111].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CsA inhibits T-helper lymphocytes, cytotoxic and inflammatory responses in macrophages, inducible nitric oxide synthase (iNOs) expression avoiding the formation of nitric oxide (NO)-derived cytotoxic species, Cox-2 mRNA accumulation, tumor necrosis factor (TNFα) production and reduces cytokines and interleukins production (IL-1, IL-2, and IL-6). Also, CsA reduced the apoptosis of SC cells and increased the protein expression levels of cyclophilin-D (Cyp-D) and apoptosis-inducing factor (AIF) [61,62]. This compound is capable of inducing motor recovery after SCI [63].…”
Section: Cyclosporine Amentioning
confidence: 99%